2007
DOI: 10.1007/s11071-006-9163-4
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear vibrations of viscoelastic cylindrical shells taking into account shear deformation and rotatory inertia

Abstract: The vibration problem of a viscoelastic cylindrical shell is studied in a geometrically nonlinear formulation using the refined Timoshenko theory. The problem is solved by the Bubnov-Galerkin procedure combined with a numerical method based on quadrature formulas. The choice of relaxation kernels is substantiated for solving dynamic problems of viscoelastic systems. The numerical convergence of the Bubnov-Galerkin procedure is examined. The effect of viscoelastic properties of the material on the response of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Khudayarov and Bandurin [4] studied the effects of the viscoelastic parameters on the nonlinear vibrations of cylindrical panels in a gas flow and showed that the viscoelastic properties have significant effect on the vibrations of the cylindrical panel. Based on the Kirchhoff-Love hypothesis, Eshmatov et al [5][6][7][8][9] investigated the linear and nonlinear vibration and dynamic stability of a viscoelastic cylinder. They considered the effect of viscoelastic properties, concentrated masses, rotary inertia, and shear deformation on the dynamic stability of a cylindrical panel.…”
Section: Introductionmentioning
confidence: 99%
“…Khudayarov and Bandurin [4] studied the effects of the viscoelastic parameters on the nonlinear vibrations of cylindrical panels in a gas flow and showed that the viscoelastic properties have significant effect on the vibrations of the cylindrical panel. Based on the Kirchhoff-Love hypothesis, Eshmatov et al [5][6][7][8][9] investigated the linear and nonlinear vibration and dynamic stability of a viscoelastic cylinder. They considered the effect of viscoelastic properties, concentrated masses, rotary inertia, and shear deformation on the dynamic stability of a cylindrical panel.…”
Section: Introductionmentioning
confidence: 99%
“…The nonlinear governing equation were solved by using the Runge-Kutta method. The vibration problem of a viscoelastic cylindrical shell in a geometrically nonlinear formulation was studied using the refined Timoshenko theory by Eshmatov [5]. He solved the equations by the Bubnov-Galerkin procedure combined with a numerical method based on the quadrature formulas.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of papers [11,12,13,14,15,16] the vibrations and dynamic stability of viscoelastic cylindrical shells and cylindrical panels, with and without concentrated masses, using the Kirchhoff-Love hypothesis and Timoshenko theories and taking into account shear deformation and rotary inertia were considered.…”
Section: Introductionmentioning
confidence: 99%